NILAI PENDIDIKAN DALAM UNGKAPAN KEPERCAYAAN MASYARAKAT JORONG LIMAU PURUIK KENAGARIAN SUNGAI NANAM KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Serli Agustin (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2021)
Based on the research that has been carried out, it can be explained that the data on expressions of public trust in Jorong Limau Puruik Kenagarian Sungai Nanam, Lembah Gumanti District, Solok Regency were obtained using the Jorong Limau Puruik or Minang language. about the expression of public trust in Jorong Limau Puruik Kenagarian Sungai Nanam, Lembah Gumanti Kabupaten Solok Regency. The researcher then recorded and recorded the expression of belief. From the results of research conducted in the field found 50 data. The purpose of educational value for the people of Jorong Limau Puruik Kenagarian Sungai Nanam, Lembah Gumanti Kabupaten Solok Regency is all areas of life, in choosing and fostering a good life in accordance with human dignity. and also as a continuous process of humanity and humanity.